Enhanced thermal conductivity in percolating nanocomposites: a molecular dynamics investigation. Issue 46 (15th November 2018) - Termentzidis, Konstantinos; Giordano, Valentina M.; Katsikini, Maria; Paloura, Eleni; Pernot, Gilles; Verdier, Maxime; Lacroix, David; Karakostas, Ioannis; Kioseoglou, Joseph
Abstract : In this work we present a molecular dynamics investigation of thermal transport in a silica–gallium nitride nanocomposite. Abstract : In this work we present a molecular dynamics investigation of thermal transport in a silica–gallium nitride nanocomposite. A surprising enhancement of the thermal conductivity for crystalline volume fractions larger than 5% is found, which cannot be predicted by an effective medium approach, not even including percolation effects, the model systematically leading to an underestimation of the effective thermal conductivity. The behavior can instead be reproduced if an effective volume fraction twice larger than the real one is assumed, which translates into a percolation effect surprisingly stronger than the usual one. Such a scenario can be understood in terms of a phonon tunneling between inclusions, enhanced by the iso-orientation of all particles. Indeed, if a misorientation is introduced, the thermal conductivity strongly decreases. We also show that a percolating nanocomposite clearly stands in a different position than other nanocomposites, where thermal transport is dominated by the interface scattering and where parameters such as the interface density play a major role, differently from our case.